Foreign direct investment, productivity and the technology gap in African economies - Christopher Malikane; Prosper Chitambara (Journal of African Trade, 2017)
This paper investigates the impact of foreign direct investment on total factor productivity conditional on relative backwardness in a panel of 45 African countries over the period 1980-2012. We use two measures of relative backwardness, namely: the distance from technological frontier and the income gap. We apply the fixed-effects and two-step system GMM methods. We find a generally positive but weak effect of FDI on productivity growth. Meanwhile, the results do not support the convergence theory of Findlay (1978) and Wang and Blomstrom (1992), that relative backwardness would result in higher productivity growth via the adoption of foreign technologies.
Keywords: E22; F21; F23; O16; 330; Foreign direct investment; Total factor productivity; Technology gap; Africa